LITERASI KEUANGAN BAGI KUBE (KELOMPOK USAHA BERSAMA) GANTARI JAYA DI KOTA DENPASAR - Wisni Arie Pramuki, Ni Made; Dewi Padnyawati, Kadek; Komang Sumadi, Ni; Yeni Yuliantari, Putu; Wayan Sudiana, I; Putu Indraswarawati, Sang (Dharma Bhakti, 2024)
This community service aims to provide financial management knowledge to business actors who are members of the Ganatri Jaya Joint Business Group (KUBE) which is facilitated by Graha Nawasena Rumah Harapan Disabled Denpasar City. The separation of personal finances and business finances is still widely mixed in their use and recording. In fact, separating personal finances from business as a form of financial management is very important to support business continuity. Financial literacy is a very important thing to provide to business actors so that they can manage their business finances well. Financial management is the key to someone's success in running their business. Remembering the importance of recording and managing finances to distinguish business assets from personal assets. The result of this service activity is that business actors become more aware of financial management in increasing income and maintaining business continuity